(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
The Timurid prince and astronomer Mirzo Ulugbek (Muhammad Taraghay Kuragan, 1394–1449) stands among the most distinguished polymath scholars produced by the medieval Islamic world. This article re-examines Ulugbek’s intellectual legacy and personal character through three principal lenses: the legislative and institutional framework through which Uzbekistan and the international community have recognised his contribution; the primary-source testimony preserved in a letter written by mathematician Ghiyasuddin Jamshid al-Kashi to his father around 1420–1421; and the broader tradition of Samarkand astronomy culminating in the Zij-i Jadid-i Guragan. The al-Kashi letter preserved in the Sipahsalar Library, Tehran, and translated into numerous languages provides uniquely intimate evidence of Ulugbek’s memorisation of the Quran and its commentaries, his mastery of Arabic grammar, his exceptional command of mathematics and observational astronomy, and his active participation in scholarly disputations at the madrasa and court. The article argues that recovering this multidimensional portrait of Ulugbek as jurist, linguist, mathematician, and ruler is essential both for accurate historiography and for the transmission of intellectual and moral heritage to younger generations.